1992
DOI: 10.1093/oxfordjournals.eurheartj.a060288
|View full text |Cite
|
Sign up to set email alerts
|

Serial Doppler echocardiographic assessment of left and right ventricular filling for non-invasive diagnosis of mild acute cardiac allograft rejection

Abstract: Detection of acute cardiac allograft rejection (AR) remains an important clinical challenge. The role of Doppler echocardiography for the non-invasive diagnosis of AR is controversial, in particular with regard to milder forms of rejection. This study was designed to evaluate the potential of Doppler echocardiography for the non-invasive diagnosis of mild AR. Serial measurements of left and right ventricular filling parameters were performed in 31 heart transplant recipients and compared with simultaneously ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Conflicting data on the association between cardiac allograft function and acute rejection have been published (17–21). Although some authors described an association between acute rejection and echocardiographic parameters at group level, the considerable overlap between individuals limits the use of echocardiography for the diagnosis of acute rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting data on the association between cardiac allograft function and acute rejection have been published (17–21). Although some authors described an association between acute rejection and echocardiographic parameters at group level, the considerable overlap between individuals limits the use of echocardiography for the diagnosis of acute rejection.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no correlation has been found between any of the echocardiographic variables and histological signs of acute allograft rejection. Because variation in pre‐ and afterload are important determinants of the transmitral flow properties, this lack of correlation can, besides the risk of false negative biopsy samples, be explained by changes in loading conditions caused by post‐transplant arterial hypertension, or by fluid retention as a result of the use of cyclosporine and prednisone (21, 22). Furthermore, the above mentioned gradual improvement in diastolic function in the early post‐operative period may conceal acute changes caused by the rejection process.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the risk of false negative biopsies and the effect of the immune response, left ventricular filling properties and heart morphology can be affected by loading conditions, hypertension, oedema resulting from ischaemia/reperfusion injury, and treatment with diuretics or vasodilators. [15][16][17][18][19] Moreover, it has been described that treatment with cyclosporin, in comparison with previous treatment strategies without calcineurin blockers, results in less pronounced morphological and functional changes during acute rejection with loss of sensitivity of echocardiographic parameters. 20 Furthermore, diastolic function parameters improve in the early postoperative period, reflecting recovery from the operative insult, which may conceal acute changes caused by the rejection process.…”
Section: Discussionmentioning
confidence: 99%